The role of oligoclonal band count and IgG index in treatment response and disease activity in multiple sclerosis - Taskiran, Esra; Terzi, Murat; Helvaci, Elif Merve; Eser, Meltem Zeycan; Avci, Bahattin; Faruk, Turan Omer; Karaibrahimoglu, Adnan (Elsevier Sci Ltd, 2024)
Background/aim: Multiple sclerosis (MS) is an inflammatory demyelinating central nervous system (CNS) disease. Among the paraclinical tests, brain and spinal Magnetic Resonance Imaging (MRI) is primarily involved in the diagnosis process, and cerebrospinal fluid (CSF) analysis is fundamental in diagnosing MS and the differential diagnosis. A positive relationship was demonstrated between oligoclonal band (OCB) positivity, CSF band number and immunoglobulin G(IgG) index. The study aimed to evaluate whether the number of OCB can predict disease activity and determine a correlation with the IgG index. Methods: Our study included 401 MS patients who had relapsing-remitting multiple sclerosis (RRMS), primary progressive multiple sclerosis (PPMS), secondary progressive multiple sclerosis (SPMS), clinic isolated syndrome (CIS), radiologic isolated syndrome (RIS), Neuromyelitis optica spectrum disorder (NMOSD) and Acute disseminated encephalomyelitis (ADEM) with OCB number groups of 2-4, 4-8, 8-12, and 12 and above. Results: No significant correlation was observed between IgG index, pre-and post-treatment EDSS (Expanded Disability Status Scale Scores) and disease-modifying therapies (DMT). Drug response was better in the patient group with band number between 2 and 8 and post-treatment EDSS scores were lower (1.62 +/- 0.44). Conclusion: The study results suggested that band number may be as valuable as the IgG index and a predictive biomarker for disease activity.
Keywords: Multiple sclerosis; Oligoclonal band number; Immunoglobulin IgG index; Disease activity; Treatment; Biomarker